1) 2+b*9-25=40
2) (c-104+2)*5+3=98
3) 11-(7*5-9*9:f:3) : 8=7
4) 22-5*(38-4*g)=12
Răspunsuri la întrebare
Răspuns de
0
1)
2 + b × 9 - 25 = 40
2 + b × 9 = 40 + 25
2 + b × 9 = 65
b × 9 = 65 - 2
b × 9 = 63
b = 63 : 9
b = 7
2)
(c - 104 + 2 ) × 5 + 3 = 98
(c - 104 + 2 ) × 5 = 98 - 3
(c - 104 + 2 ) × 5 = 95
c - 104 + 2 = 95 : 5
c - 104 + 2 = 19
c = 19 - 2 + 104 → metoda mersului invers
c = 17 + 104
c = 121
3)
11 - ( 7 × 5 - 9 × 9 : f : 3 ) : 8=7
(35 - 81 : f : 3) : 8 = 11 - 7
(35 - 81 : f : 3) : 8 = 4
35 - 81 : f : 3 = 4 x 8
35 - 81 : f : 3 = 32
81 : f : 3 = 35 - 32
81 : f : 3 = 3
81 : f = 3 x 3
81 : f = 9
f = 81 : 9
f = 9
4)
22 - 5 × (38 - 4 x g) = 12
5 × (38 - 4 x g) = 22 - 12
5 × (38 - 4 x g) = 10
38 - 4 x g = 10 : 5
38 - 4 x g = 2
4 x g = 38 - 2
4 x g = 36
g = 36 : 4
g = 9
2 + b × 9 - 25 = 40
2 + b × 9 = 40 + 25
2 + b × 9 = 65
b × 9 = 65 - 2
b × 9 = 63
b = 63 : 9
b = 7
2)
(c - 104 + 2 ) × 5 + 3 = 98
(c - 104 + 2 ) × 5 = 98 - 3
(c - 104 + 2 ) × 5 = 95
c - 104 + 2 = 95 : 5
c - 104 + 2 = 19
c = 19 - 2 + 104 → metoda mersului invers
c = 17 + 104
c = 121
3)
11 - ( 7 × 5 - 9 × 9 : f : 3 ) : 8=7
(35 - 81 : f : 3) : 8 = 11 - 7
(35 - 81 : f : 3) : 8 = 4
35 - 81 : f : 3 = 4 x 8
35 - 81 : f : 3 = 32
81 : f : 3 = 35 - 32
81 : f : 3 = 3
81 : f = 3 x 3
81 : f = 9
f = 81 : 9
f = 9
4)
22 - 5 × (38 - 4 x g) = 12
5 × (38 - 4 x g) = 22 - 12
5 × (38 - 4 x g) = 10
38 - 4 x g = 10 : 5
38 - 4 x g = 2
4 x g = 38 - 2
4 x g = 36
g = 36 : 4
g = 9
Alte întrebări interesante
Biologie,
8 ani în urmă
Franceza,
8 ani în urmă
Franceza,
8 ani în urmă
Matematică,
9 ani în urmă
Engleza,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă